2008
DOI: 10.1080/09291010701424812
|View full text |Cite
|
Sign up to set email alerts
|

12-hour phase-shift of mice kidney rhodanese (thiosulfate sulfurtransferase) activity in the first two months of life

Abstract: This study aimed to investigate and compare variation of renal rhodanese activity at 2 nd , 4 th and 8 th weeks of post-natal development (PND) in mice. The enzyme activity increased with age and was higher in females compared to males in all studied groups. Cosinor analysis revealed significant circadian rhythms (with period t ¼ 24 h) of enzyme activity in both genders with peak time shift during the PND. At the 2 nd week of PND (pre-weaning time), the circadian rhythm peaked at the beginning of light span, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…But then, in addition, it is necessary to demonstrate a reasonable relation between the waveforms of the temporal patterns of drug levels and their effects. In our previous studies, daily variations of rhodanese, a principal enzyme of cyanide (considered as responsible of SNP toxicity) detoxification, were observed in various tissues, including the liver [ 9 - 11 ]. However, there was no correlation between SNP-induced neurotoxicity and the temporal variations of enzyme activities, suggesting that the toxicity of SNP is not only mediated by cyanide, and/or that the enzyme rhodanese is not the only one playing a role in cyanide detoxification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But then, in addition, it is necessary to demonstrate a reasonable relation between the waveforms of the temporal patterns of drug levels and their effects. In our previous studies, daily variations of rhodanese, a principal enzyme of cyanide (considered as responsible of SNP toxicity) detoxification, were observed in various tissues, including the liver [ 9 - 11 ]. However, there was no correlation between SNP-induced neurotoxicity and the temporal variations of enzyme activities, suggesting that the toxicity of SNP is not only mediated by cyanide, and/or that the enzyme rhodanese is not the only one playing a role in cyanide detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian peak and trough times of ataxia in 8 week old animals matched well with the observed maximum and minimum of oxidative effects after SNP (2.5 mg.kg -1 ) injection at the early light and dark spans, respectively [ 39 ]. However, the high sensitivity of male mice compared to females matched the observed high levels of rhodanese in females [ 9 - 11 ], indicating partially the great influence of cyanide on SNP-induced toxicity. On the other hand, these results revealed that there were opposite effects depending on the time of administration in SNP-induced neurotoxicity, illustrating that there are not only quantitative differences in drug effects.…”
Section: Discussionmentioning
confidence: 99%